The SCPA framework: an observation-based formative assessment model for inclusive children's oral language development - Fitra Afrida Amna; Syahrul Ramadhan (Jurnal Konseling dan Pendidikan, 2026)
Current assessment paradigms don't take account of the mediated, multi-modal, and ecologically embedded nature of language development in CSN, they are theoretically unsuited for inclusive educative conditions. The Sociocultural Psychological Academic (SCPA) Assessment Framework, a book, conceptually based model for assessing language development in inclusive early childhood education, is suggested and validated empirically in this study. This is implemented at TK Ar-Razzaq Al-Mughni, Padang, West Sumatra. Four iterative cycles of an mixed methods design in participatory action research (PAR) was employed. Eleven CSN parents, two teachers, and 15 field coordinators attended. Quantitative data from pre-test/post-test analysis of a validated 30-item questionnaire (Cronbach's alpha = 0.81–0.87); qualitative data from four focus group discussions (60–75 minutes each, audio recorded and verbatim transcribed); structured observational checklists; and documentary analysis, every one of that were analyzed according to thematic analysis. Validity was guaranteed by triangulation across data sources. Four theoretical pillars have been integrated to the SCPA framework: Feuerstein's Mediated Learning Experience theory, Bronfenbrenner's ecological systems model, Vygotsky's sociocultural theory (Zone of Proximal Development), and Universal Design for Learning. An overall mean knowledge gain of 43.72% across assessment domains (sociocultural: 46.55%; psychological: 50.00%; academic/UDL: 35.38%) was discovered in pre-test/post-test analysis. Qualitative studies revealed systematic shifts in language mediation quality, institutional assessment culture, and parental assessment literacy from deficit oriented to potential-oriented assessment paradigms. Conclusion: With implications for preparation for teachers, assessment changes in policy, and future research in the ASEAN region, the SCPA Framework represents a theoretically sound and practically demonstrated innovation in language learning assessment for inclusive early childhood education in Indonesia.